Case Based Reasoning in Engineering Design - Gozali, Ferrianto (Jurnal Teknik Elektro, 2002)
Design is an activity that requires not only fundamental knowledge in the domain of theapplication and understanding of the interactions with other aspects such as ergonomic,economic, technical and social but also creativity of designers. To generate innovativesolutions, expert designers often use their experiences, the history of failed as well assuccessful designs, as a valuable information source to help them to solve a current designproblem. For beginners, such information is even more valuable. Thus, experiences earnedfrom previous design processes can be a rich source of ideas and inspiration in every stageof design. Case-based reasoning or CBR is a methodology in automated reasoning andmachine learning. In CBR, a reasoner solves a new problem by searching for the similarityof the problem to one or several previously solved problems stored as cases in the case baseand then adapting their known solutions instead of working out a solution from scratch.Designers analyse the design problem through formal methods, but creating a new designrequires previous experiences, or at least, exposure to anothers design experiences. InCase-based design, CBR supports a design process by reminding designers of previousdesign experiences that can help to solve new design problems. This paper describes apreliminary survey of CBR application in design to support the research of CBR applicationin engineering design education. A CBR basic concept will be explored first followed by ageneral step of engineering design process. It is also described issues raised by theapplication of CBR in design process, and finally we propose the possibilities of introducinga CBR method in engineering design education.Keywords: Case Based Reasoning, Engineering Design, Design Case, Case Base.